Improvement of folate biosynthesis by lactic acid bacteria using response surface methodology - Muhamad Nor, Norfarina; Mohamad, Rosfarizan; Foo, Hooi Ling; Abdul Rahim, Raha (Faculty of Food Technology and Biotechnology, University of Zagreb, Croatia, 2010)
Lactic acid bacteria (Lactococcus lactis NZ9000,Lactococcus lactis MG1363, Lactobacillus plantarum I-UL4 and Lactobacillus johnsonii DSM 20553) have been screened for their ability to produce folate intracellularly and/or extracellularly. L. plantarum I-UL4 was shown to be superior producer of folate compared to other strains. Statistically based experimental designs were used to optimize the medium formulation for the growth of L. plantarum I-UL4 and folate biosynthesis. The optimal values of important factors were determined by response surface methodology (RSM). The effects of carbon sources, nitrogen sources and para-aminobenzoic acid (PABA) concentrations on folate biosynthesis were determined prior to RSM study. The biosynthesis of folate by L. plantarum I-UL4 increased from 36.36 to 60.39 mg/L using the optimized medium formulation compared to the selective Man de Rogosa Sharpe (MRS) medium. Conditions for the optimal growth of L. plantarum I-UL4 and folate biosynthesis as suggested by RSM were as follows: lactose 20 g/L, meat extract 16.57 g/L and PABA 10 mM.